EFEKTIVITAS YURISDIKSI MAHKAMAH PIDANA INTRNASIONAL (INTERNATIONAL CRIMINAL COURT) DALAM MENCEGAH IMPUNITAS - Arafat, Muhammad Rusli (UIR Press, 2024)
The long history of international criminal law enforcement above is one form of the international community's concern for victims of international crimes, because in practice, it is sometimes not easy to rely on national legal mechanisms and institutions to deal with international crime situations, because international crimes can be committed by individuals who politically have power in a country, so that national courts are expected Prosecuting and dealing with international crimes committed may be in a situation of not being able to perform the expected role. By Rome Statute of the International Criminal Court 1998, International Criminal Court It has four types of jurisdictions, namely:1) Personal Jurisdiction (ratione personae); 2) criminal/material jurisdiction (ratione materiae); 3) Territorial Jurisdiction (ratione loci); dan 4) Temporal jurisdiction (ratione temporis). The jurisdiction that the ICC has in prosecuting, prosecuting and prosecuting perpetrators of crimes in preventing impunity is still ineffective because it still has factors or reasons that make perpetrators of crimes can enjoy impunity or be free from prosecution and legal responsibility for their actions